Tingkat Kecemasan Keluarga Pasien yang Dirawat di Ruangan ICU Rumah Sakit Santa Elisabeth Medan - Siringoringo, Eny Elfrida; Sigalingging, Vina Yolanda (Prodi Keperawatan Purwokerto, 2023)
Background: While the patient is being treated in the ICU, the patient's family experiences difficulties in helplessness, temporary separation from the family, feelings of grief, feelings of hopelessness, resting and sleeping, and various emotions that can arise as reactions in each person.Â Objective: This study aims to determine the level of anxiety of the families of patients treated in the ICU at Santa Elisabeth Hospital, Medan.Â Methods: The type of research design used is quantitative with a descriptive design with a sample size of 32 people. The sampling technique used was total sampling. The research was conducted January-February 2023. The Zung Self-Rating Anxiety Scale (ZSAS) questionnaire was used to measure anxiety levels.Â Results: The results showed that the majority of respondents had a severe level of anxiety, namely 29 people (90.60%) and 2 people (6,30%) was panic. Conclusion: The results of this study showed that the majority showed severe anxiety. Researchers recommend that families always have positive thoughts by increasing spirituality and improving coping so that the anxiety experienced can be reduced.